The Public Narrative of the Johnny Depp Case on Social Media X (Twitter) - Pravidya Salsabiila; Hasfi, Nurul (Institut Komunikasi dan Bisnis LSPR, 2024)
The netizen's narrative of the Johnny Depp and Amber Heard case became a controversy and developed on social media X (Twitter). Patriarchal cultural beliefs and traditions that emphasize male assertiveness and dominance over women influence the construction of masculinity in the issue of domestic violence. The researcher attempted to capture the diversity of perspectives by exploring the complexity of netizen's narratives on the issue of violence experienced by men. The purpose of this article is to highlight the relationship between socio-cultural constructions of patriarchy, masculinity, and domestic violence through the case of Johnny Depp. By adopting the dominant patriarchal perspective in Indonesia. This research reveals that masculine and feminine gender roles have implications for netizen's understanding of the stereotypical assignment of perpetrators and victims in domestic violence cases. The diversity of comment on the Johnny Depp and Amber Heard case produces narratives that can have an impact on perpetrators and survivors of domestic violence. Patriarchy and masculinity need to show engagement for men as support and care for male survivors. Virtual ethnography research method is used to provide an impressionistic picture based on public reality through the internet. This study concludes that netizen’s narratives about domestic violence need to be viewed using gender neutrality as an effort to avoid partiality to a particular gender.